Influence of continuous magnetic field on the performance of molecularly imprinted polymers - Guerreiro, Antonio R.; Korkhov, Vadim; Mijangos, Irene; Piletska, Elena V.; Rodins, Juris; Turner, Anthony P. F.; Piletsky, Sergey A. (Elsevier Science B.V., Amsterdam., 2008)
A set of polymers was imprinted with (−)-ephedrine using UV initiation, under the influence of a constant external magnetic field with intensities ranging from 0 to 1.55 T. Synthesised materials were characterised by X-ray crystallography, infrared spectroscopy, swelling and surface area. Recognition properties were assessed by the ability to discriminate between (+) and (−)- ephedrine and by Scatchard analyses on chromatographic mode. It was shown that polymer morphology and recognition properties are affected by the magnetic field. This resulted in considerable improvements in the chromatographic resolution of ephedrine enantiomers by materials synthesised under the influence of magnetic field. Apparently the magnetic field improved the ordering of the polymer structure and facilitated the formation of more uniform imprinting s
Keywords: Molecularly imprinted polymers; Magnetic field polymerisation